2019
DOI: 10.3390/app9102100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intensity- and Polarization-based Contrast in Amyloid-beta Plaques as Observed by Optical Coherence Tomography

Abstract: One key hallmark of Alzheimer’s disease (AD) is the accumulation of extracellular amyloid-beta protein in cortical regions of the brain. For a definitive diagnosis of AD, post-mortem histological analysis, including sectioning and staining of different brain regions, is required. Here, we present optical coherence tomography (OCT) as a tissue-preserving imaging modality for the visualization of amyloid-beta plaques and compare their contrast in intensity- and polarization-sensitive (PS) OCT. Human brain sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It has also been previously concluded that not all plaques are visible by either contrast modality. 60 Hence negative OCT findings do not rule out the presence of retinal Aβ plaques. Even if plaques could be seen in the retina with OCT, it would be difficult to distinguish them from the HRF and the depolarizing deposits which are already present in these retinas as observed in Fig.…”
Section: Cortical Amyloid Beta Plaque Loadmentioning
confidence: 99%
“…It has also been previously concluded that not all plaques are visible by either contrast modality. 60 Hence negative OCT findings do not rule out the presence of retinal Aβ plaques. Even if plaques could be seen in the retina with OCT, it would be difficult to distinguish them from the HRF and the depolarizing deposits which are already present in these retinas as observed in Fig.…”
Section: Cortical Amyloid Beta Plaque Loadmentioning
confidence: 99%
“…As described by Gesperger et al, multiple single plaques in the immediate vicinity detected by histology might also be mistaken for a single, large plaque due to the limited resolution of our OCT setup. 23 Therefore, our OCT setup might not be capable of visualizing all amyloid plaques. Further, the contrast in OCT images depends on the detected scattering signal, which in the case of the amyloid-beta plaques depends on the shape, size, and composition of these structures.…”
Section: Discussionmentioning
confidence: 99%
“…18 A polarization sensitive (PS)-OCM setup at 840 nm was later utilized to identify plaques in postmortem brain tissue based on their intrinsic birefringence. 19 Recently, Gesperger et al 23 conducted a study using a commercial PS-OCT setup to categorize A-β plaques depending on their inherent intensity and PS signal. Using visible light OCT, A-β plaques in murine and human brain tissue down to a diameter of 10 μm were visualized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations